A computational spinal motion segment model incorporating a matrix composition-based model of the intervertebral disc. (February 2016) - Barthelemy, V.M.P.; van Rijsbergen, M.M.; Wilson, W.; Huyghe, J.M.; van Rietbergen, B.; Ito, K.
Abstract: The extracellular matrix of the intervertebral disc is subjected to changes with age and degeneration, affecting the biomechanical behaviour of the spine. In this study, a finite element model of a generic spinal motion segment that links spinal biomechanics and intervertebral disc biochemical composition was developed. The local mechanical properties of the tissue were described by the local matrix composition, i.e. fixed charge density, amount of water and collagen and their organisation. The constitutive properties of the biochemical constituents were determined by fitting numerical responses to experimental measurements derived from literature. This general multi-scale model of the disc provides the possibility to evaluate the relation between local disc biochemical composition and spinal biomechanics. Graphical abstract: Highlights: Development of a biochemical composition-based disc model in a L3–L4 SMS. The material model captures the annulus and nucleus tissue behaviour. The model predicts realistic ranges of motion for the spinal motion segment. The model can simulate motion segment mechanics based on local tissue composition.